Throughput behavior of reliable stream protocols in admission controlled bearer networks. - Meempat, Gopalakrishnan (Computer networks and ISDN systems.)
This paper conducts an investigation of the application level behavior of feed forward rate control mechanisms in broadband networks. Specifically, some potential problems which can have a pronounced impact on performance are identified, by studying the behavior of the Transmission Control Protocol (TCP) overlayed above a generic rate controlled bearer network. Our conclusions, based on some theoretical models in a simulation experiment, demonstrate that under the strict policing approach for rate control, even minor variations in the traffic characteristics or network response can potentially lead to significant degradation in the application level performance. It is further shown that the adoption of the buffered form of rate control, or traffic shaping, instead of strict policing can alleviate this problem to a significant extent.